COMPARATIVE ANALYSIS OF IMPACTS OF VARIOUS JAMMING ATTACKS ON 5G NETWORK - Tiamiyu, Osuolale Abdramon; Babatunde , Abdulrauph Olanrewaju; Kamardeen, Muhammad Dayo (FUDMA JOURNAL OF SCIENCES, 2024)
With the promise of faster data speeds and more dependable service, fifth-generation (5G) wireless cellular networks are encouraging the adoption of cutting-edge technologies like smart cities and the Internet-of-things (IoTs). However, 5G networks are susceptible to possible interference because of their open-sharing principles, especially from malicious jamming attacks. Notwithstanding, for further notable progress in 5G technology, thorough simulations and studies are imperative to properly comprehend the fundamentals of jamming attacks on 5G networks. To close this gap, this study simulated and analyzed jamming attacks on 5G communication systems to determine how these attacks affect important 5G performance indicators and assessed and suggested remedies that will maximize 5G network resilience against jamming.